2012
DOI: 10.1007/s10792-011-9503-3
|View full text |Cite
|
Sign up to set email alerts
|

Primary cutaneous adenoid cystic carcinoma of the upper lid: a case report and literature review

Abstract: To report on the diagnostic challenge of an adenoid cystic carcinoma arising from the eyelid. A 77-year-old male was referred to our center with a clinical diagnosis of upper eyelid chalazion for a lesion that had appeared 2 years before. A loss of cilia was observed over the cutaneous area of induration, but there was no reddening or ulceration. Incisional biopsy was performed and the specimen was submitted in formalin for histopathological examination. On light microscopy, the lesion was composed of basaloid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 8 publications
0
17
1
Order By: Relevance
“…Cacchi et al (6) reported that the diagnosis of PCACC is typically made approximately 10 years after onset and at a patient mean age of 59 years. While Cavazza et al (1) reported that ACC of the eyelid characteristically emerges with painful nodules together with eyelash loss or irregularity, the mass lesion observed in our case was small and not accompanied by any significant eyelash changes or nodules. We hypothesize that this diffe rence in appearance resulted from the establishment of diagnosis four rather than 10 years after onset and when the patient was 52 rather than 59 years of age.…”
Section: Discussioncontrasting
confidence: 72%
See 4 more Smart Citations
“…Cacchi et al (6) reported that the diagnosis of PCACC is typically made approximately 10 years after onset and at a patient mean age of 59 years. While Cavazza et al (1) reported that ACC of the eyelid characteristically emerges with painful nodules together with eyelash loss or irregularity, the mass lesion observed in our case was small and not accompanied by any significant eyelash changes or nodules. We hypothesize that this diffe rence in appearance resulted from the establishment of diagnosis four rather than 10 years after onset and when the patient was 52 rather than 59 years of age.…”
Section: Discussioncontrasting
confidence: 72%
“…Analysis of these pathological findings resulted in the diagnosis of PCACC. the origin of the remaining three was not reported (1,7) . Cavazza et al (1) concluded that both eyelids were equally involved, as four cases developed from the upper eyelid and four from the lower eyelid.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations